2020
DOI: 10.3390/jcm9041207
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and Character Traits of Female Eating Disorder Patients with(out) Non-Suicidal Self-Injury

Abstract: Eating disorder (ED) patients show alarmingly high prevalence rates of Non-Suicidal Self-Injury (NSSI). Adolescents seem to be particularly at risk, as EDs and NSSI both have their onset in mid-adolescence. It has been suggested that personality could be a transdiagnostic mechanism underlying both EDs and NSSI. However, little attention has been given to adolescent clinical samples compared to adult and/or community samples. Therefore, the current study investigated the role of personality in a sample of 189 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 75 publications
0
11
0
1
Order By: Relevance
“…Apart from a higher prevalence of lifetime NSSI in patients with ED, the extent of severe and recent NSSI is probably also higher in patients with ED compared to community adults. A recent study of Buelens et al ( 2020 ), identified different temperamental characteristics in patients with ED reporting only lifetime NSSI versus patients with ED also reporting recent NSSI. Consequently, including measurements of recent NSSI in future research is suggested to improve understanding about NSSI and its underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from a higher prevalence of lifetime NSSI in patients with ED, the extent of severe and recent NSSI is probably also higher in patients with ED compared to community adults. A recent study of Buelens et al ( 2020 ), identified different temperamental characteristics in patients with ED reporting only lifetime NSSI versus patients with ED also reporting recent NSSI. Consequently, including measurements of recent NSSI in future research is suggested to improve understanding about NSSI and its underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SIB could not be resolved effectively in all monkeys with a standard treatment regimen. In a similar vein, both the presence and severity of NSSI covary with many different factors such as temperament ( Buelens et al, 2020 ) and early life stress exposure ( Cassels et al, 2018 ).…”
Section: Challenges To the Study Of Self-injury In Humans And Monkeysmentioning
confidence: 97%
“…Moreover, 50-75% of those with a history of NSSI make a suicide attempt at some point in their life (9). Research has shown how NSSI can occur with virtually any mental disorder, although comorbidity rates are particularly high for anxiety and mood disorders, post-traumatic stress disorder, substance use disorder, eating disorders, and personality disorders (10)(11)(12). The high prevalence rates and significant mental health implications underscore the necessity for an improved understanding of NSSI (13).…”
Section: Introductionmentioning
confidence: 99%